PHYSICAL ATTRACTIVENESS BEAUTY INFLUENCER PADA INTERAKSI PARASOSIAL: APAKAH MEMPENGARUHI PURCHASE INTENTION FOLLOWER? - Palupi, Inten; Kurniawati, Kurniawati; Masnita, Yolanda (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.01.TAHUN.2024DO - 10.24843/EEB.2024.v13.i01.p06, 2024)
The demand for beauty products in Indonesia has been increasing. This ultimately encourages consumers to seek further information about the products they intend to purchase, one of which is through beauty Influencer recommendations on Instagram, considering that the social media platform offers a lot of content featuring beauty Influencers' recommendations. However, the reality is that the relationship between followers and Influencers has not been successful in persuading followers to buy the products reviewed or recommended. Based on this phenomenon, this research examines and analyzes the influence of parasocial interaction (PSI) on the purchase intention of followers and its implications. This study presents four hypotheses. The results of this research indicate that the social attractiveness and expertise of Beauty Influencers influence parasocial interaction, and parasocial interaction influences followers' long-term intention to purchase beauty products. However, the physical attractiveness of Beauty Influencers was not found to have an impact on PSI.